Pemberian Terapi Rebusan Daun Salam Terhadap Penurunan Tingkat Nyeri Akibat Hipertensi - Novia Salsabila; Ridha Hidayat; Gusman Virgo (Excellent Health Journal, 2025)
If hypertension sufferers do not regularly check their blood pressure, they will not realize that they have high blood pressure because generally hypertension sufferers do not experience any signs and symptoms. The purpose of this study is to provide family nursing care to Mrs. N by administering bay leaf decoction therapy to reduce pain levels due to hypertension in Kualu Nenas Village, the working area of ​​the Tambang Community Health Center (UPT). This study uses a descriptive research method in the form of a case study with a nursing care approach. This study was conducted on June 22-28, 2025 with 1 respondent in one family conducted at the client's home. From the case analysis on the client, it was found that there was a decrease in pain levels and blood pressure after being given bay leaf decoction therapy, on the first day the pain level was 6 then decreased to 2 on the seventh day while the results of the blood pressure examination on the first day from 211/129 mmHg decreased to 144/93 mmHg on the seventh day. It is hoped that clients and families will always pay attention to their health, check their blood pressure regularly and carry out non-pharmacological therapy, one of which is bay leaf decoction therapy.